Studi Tentang Teori-Teori Hukum Islam yang Berhubungan dan Mendukung Keberadaan Peradilan Agama di Indonesia - Sirman Dahwal; Dimas Dwi Arso (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
It is necessary to study Islamic legal theories that relate to and support the Religious Courts in Indonesia as Islamic family courts that grow and develop in resolving disputes fairly, especially for the Indonesian Muslim community. This writing aims to discuss legal theories that support the existence of the Religious Courts in Indonesia and the history of the Religious Courts in Indonesia from before independence until now. The method in this research is normative legal research. The discussion is directed to material analysis of Islamic legal theories and the arguments and principles of fiqh, which form the basis of thinking. The results of research on the existence of the Religious Courts in Indonesia are proven by supporting legal theory, receptive in complex theory, reception theory, sensory exit theory, receptive a contrario theory and other theories that have developed to help the existence of the Religious Courts and existing regulations such as Law no. 7 of 1989 which has been amended by Law no. 3 of 2006, then amended again by Law no. 50 of 2009 concerning the Religious Courts and Compilation of Islamic Law with Presidential Decree No. 1 of 1991, as well as Decree of the Minister of Religion No. 154 of 1991 concerning the Implementation of the Compilation of Islamic Law, it is hoped that a new chapter will begin for the History of the Development of the Religious Courts in Indonesia. Saat ini perlu dikaji teori-teori hukum Islam yang berhubungan dan mendukung Peradilan Agama di Indonesia sebagai peradilan keluarga Islam yang tumbuh berkembang dalam menyelesaikan sengketa secara adil, khususnya bagi masyarakat muslim Indonesia. Adapun tujuan penulisan ini yaitu membahas Teori-teori hukum yang mendukung keberadaan Peradilan Agama di Indonesia, dan sejarah Peradilan Agama di Indonesia sejak sebelum kemerdekaan hingga sekarang ini. Metode dalam penelitian ini adalah penelitian hukum normatif. Pembahasan diarahkan kepada analisis materi teori-teori hukum Islam serta dalil-dalil dan kaidah-kaidah fikih yang menjadi landasan berpikir. Adapun hasil penelitian keberadaan Peradilan Agama di Indonesia dibuktikan dengan teori hukum yang mendukung, teori receptie incomplexu, teori receptie, teori receptie exit, teori receptie a contrario dan teori lain yang berkembang mendukung keberadaan Peradilan Agama serta peraturan yang eksis seperti Undang-undang No. 7 Tahun 1989 yang telah diubah dengan dengan Undang-undang No. 3 Tahun 2006, kemudian diubah lagi dengan Undang-undang No. 50 Tahun 2009 tentang Peradilan Agama dan Kompilasi Hukum Islam dengan Inpres No. 1 Tahun 1991, serta Keputusan Menteri Agama No. 154 Tahun 1991 tentang Pelaksanaan Kompilasi Hukum Islam, diharapkan mulai babak baru bagi Sejarah Perkembangan Peradilan Agama di Indonesia.